The Relationship Between Knowledge, Attitudes, and Motivation with Unsafe Actions on Harper Hotel Construction Workers in Kupang City - Clara Bota Ayu kedang; Noorce Ch Berek; Johny A. R. Salmun (Lontar : Journal of Community Health, 2023)
Unsafe actions are failures to follow proper work requirements and procedures, resulting in work accidents. This study analyzes the relationship between knowledge, attitudes, and motivation with unsafe actions on construction workers at the Harper Hotel, Kupang City. This research is an analytic study with a cross-sectional design. The population in this study was 54 construction workers with a sample of 35 people who were determined based on a simple random sampling technique. The analysis in this study used the chi-square test with a significance level of 0.05. The results showed that knowledge (95% CI= 0.332 to 0.856; p=0.001), attitude (95% CI= 0.493 to 0.902; p=0.027), and motivation (95% CI= 0.513 to 907; p=0.031) had a significant relationship with unsafe actions; therefore, workers must have self-awareness about occupational safety and health against unsafe actions and use Personal Protective Equipment in the workplace to reduce the number of workplace accident.